Elementary Science Learning at the Intersection of Educational Philosophies: Rethinking Pedagogical Paradigms and Practices - Supriyati Fatma Rabia; Wahono Widodo; Hendratno Hendratno; Suryanti Suryanti (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to map how the educational philosophies of constructivism, progressivism, pragmatism, and humanism shape pedagogical paradigms and teaching practices in elementary science education. It also seeks to develop an integrative conceptual framework that supports meaningful and student-centered science learning in 21st-century primary education. Methodology: This study employed a qualitative Systematic Literature Review (SLR) following PRISMA guidelines. Articles were retrieved from the Scopus and Web of Science (WoS) databases covering the 2015–2025 period. Ten peer-reviewed articles were selected after identification, screening, and eligibility stages. Data were analyzed using thematic analysis and narrative synthesis supported by a structured data extraction instrument. Main Findings: Constructivism promotes active knowledge construction through inquiry-based approaches such as CIBSE. Progressivism emphasizes student-centered and adaptive learning environments supported by digital technology. Pragmatism integrates cultural and empirical knowledge through experiential reflection, while humanism supports holistic development by addressing affective and social dimensions. Effective science learning emerges from the interaction of these traditions rather than reliance on a single paradigm. Novelty/Originality of this study: The study synthesizes four philosophical traditions into a unified Integrative Philosophical Framework, which has rarely been explored in previous SLR studies. The findings encourage educators to adopt a reflective multi-philosophical approach. However, the review is limited by its small sample size and reliance on predominantly English-language sources. Future research should involve longitudinal mixed-methods studies across a broader range of educational contexts.